Nematode species densities, root damage and yield of bananas (Musa spp) in Uganda - Elsen, A.; Speijer, P.; Swennen, Rony L.; Waele, D. de (2000)
Host plant response to root nematodes of 'Matoke' (Musa AAA-group), 'Sukali Ndizi' (Musa AB-group) and 'Kayinja'banana (Musa ABB-group) was evaluated at lkulwe and Ryeru in Uganda. Radopholus similis and Helicotylenchusmulticinctus were the most abundant nematode species at Ikulwe. The population densities of R. similis and H. multicinctus did not differ, but the roots of 'Sukali Ndizi' and 'Kayinja' were significantly more necrotic than those of 'Matoke'. R, similis and Meloidogyne spp. population densities were positively correlated with root damage and negatively with bunch mass of 'Matoke'. Pratylenchus goodeyi was predominant in Ryeru and the population was higher in 'Matoke' than in 'Sukali Ndizi'. P. goodeyiwas negatively correlated with bunch mass of 'Matoke', but not with bunch mass of 'Sukali Ndizi' or 'Kayinja'. The relatively high susceptibility and sensitivity of 'Matoke' to R. simi/is,H. multicinctus, P. goodeyi and Meloidogyne spp. may be the underlying reason for the gradual replacement of 'Matoke' landraces by landraces of the AB- and ABB-groups.